2004
DOI: 10.1021/ac034913y
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mutation Detection in a Polymer Microfluidic Network Using Temperature Gradient Gel Electrophoresis

Abstract: A miniaturized system for DNA mutation analysis, utilizing temperature gradient gel electrophoresis (TGGE) in a polycarbonate (PC) microfluidic device, is reported. TGGE reveals the presence of sequence heterogeneity in a given heteroduplex sample by introducing a thermal denaturing gradient that results in differences between the average electrophoretic mobilities of DNA sequence variants. Bulk heater assemblies are designed and employed to externally generate temperature gradients in spatial and temporal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 21 publications
(43 reference statements)
0
54
1
Order By: Relevance
“…Meanwhile, unconjugated EtBr itself will cause a high-fluorescence background and interferes with the detection sensitivity. 23,44,45 Although our preliminary clinical investigation is limited because of restricted access to more CRC samples, the results of our study showed that the detection accuracy rate reached 100% after verification by clone sequencing. The high accuracy might be due to the relatively high sensitivity of this method, because the mutations harbored in stools can be as little as 1% in general, 11 which is much higher than the threshold concentration (0.2%) of this chip-based TGCE method.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Meanwhile, unconjugated EtBr itself will cause a high-fluorescence background and interferes with the detection sensitivity. 23,44,45 Although our preliminary clinical investigation is limited because of restricted access to more CRC samples, the results of our study showed that the detection accuracy rate reached 100% after verification by clone sequencing. The high accuracy might be due to the relatively high sensitivity of this method, because the mutations harbored in stools can be as little as 1% in general, 11 which is much higher than the threshold concentration (0.2%) of this chip-based TGCE method.…”
Section: Discussionmentioning
confidence: 70%
“…However, the large external heater assemblies in their spatial format increased difficulty with respect to accuracy control and miniaturization. 23 In our previous work, a chip-based CE platform integrated with a slantwise radiative heating system that was able to establish spatial temperature gradient using simple peripheral equipment and manipulation was developed for very simple, reliable, and cost-effective DNA mutation detection by chipbased TGCE. Various SNP samples and K-ras gene mutations in six colon cancer cell lines were successfully detected rapidly within 6 min.…”
mentioning
confidence: 99%
“…Microwave heating is also very attractive than other alternatives for obtaining spatial temporal temperature gradients for a variety of on-chip applications, including investigation of thermophoresis (Duhr et al, 2006), control and measurement of enzymatic activity (Arata et al, 2005;Mao et al, 2002;Tanaka et al, 2000), investigation of the thermodynamics (Baaske et al, 2007;Mao et al, 2002), chemical separation (Buch et al, 2004;Huang et al, 2002;Ross et al, 2002;Zhang et al, 2007), and of the kinetics characterizing molecular associations (Braun et al, 2003;Dodge et al, 2004). Most techniques for generating on-chip temperature gradients integrate Joule heating elements to conduct heat into microchannels/microchambers (Arata et al, 2005;Buch et al, 2004, Selva et al, 2009).…”
Section: Advantages Of Microwave Dielectric Heating Of Microfluidic Dmentioning
confidence: 99%
“…Most techniques for generating on-chip temperature gradients integrate Joule heating elements to conduct heat into microchannels/microchambers (Arata et al, 2005;Buch et al, 2004, Selva et al, 2009). However, temporal control is limited by the heat capacity of the microfluidic device and thermal coupling of the device to the heating elements.…”
Section: Advantages Of Microwave Dielectric Heating Of Microfluidic Dmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Several types of chips has been introduced for the postgenomic researches such as DNA/RNA chips [28][29][30][31] and the serial analysis of gene expression. [32][33][34][35] The viscosity of the separation media is one important factor for chip separation since the bounded microfluidic devices can not withstand high loading pressure.…”
Section: Introductionmentioning
confidence: 99%